HUBUNGAN PENGGUNAAN GADGET TERHADAP PERKEMBANGAN BALITA USIA 1-5 TAHUN DI POSYANDU FLAMBOYAN WILAYAH KERJA PUSKESMAS KASIHAN II - Karina Dyah Exniaputri; Sri Ratna Ningsih; Yekti Satriyandari (Jurnal Medicare, 2026)
Gadget use is increasing along with technological developments in the digital era, raising concerns about its impact on under-five children development, particularly those aged 1-5, which is considered the golden age. If gadget use is not controlled by restrictions and parental supervision, it has the potential to impact under-five children development, particularly in fine motor skills, speech and language, socialization, independence, and gross motor skills. To determine the relationship between gadget use and the development of under-five children the Posyandu (Integrated Health Post) Flamboyan. This study employed quantitative methods with a cross-sectional design. Data analysis performed was the Spearman's Rho test. The sample selected in this study was 63 under-five children aged 1-5, obtained using total sampling. Data collection utilized was a gadget use questionnaire and a Developmental Pre-Screening Questionnaire (KPSP-Kuesioner Pra Skrining Perkembangan). The Spearman's Rho correlation test yielded a p-value (sig) of 0.168 > 0.05. There is no relationship between gadget use and the development of under-five children aged 1-5 years at the Posyandu Flamboyan in the Puskesmas (Community Health Center) Kasihan II working area.